Wide band gap and conducting tungsten carbide(WC) thin films prepared by hot wire chemical vapor deposition(HW-CVD) method - Pawbake, Amit; Waykar, Ravindra; Jadhavar, Ashok; Kulkarni, Rupali; Waman, Vaishali; Date, Abhijit; Late, Dattatray J.; Pathan, Habib; Jadkar, Sandesh (Materials Letters, 2016)
In this letter, we report synthesis of tungsten carbide (WC) thin films having wide band gap(3.22-3.3 eV) with high electrical conductivity (80-1260 S/cm) by HW-CVD using heated using heated W filament and Tetra-fluoro-methane (CF4) gas. Formation of WC was confirmed by low angle XRD, Raman spectroscopy and x-ray photoelectron spectroscopy. UV-Visible spectroscopy analysis revealed that the synthesized films have high transmission at wavelength 500 nm. Electrical properties measured using Hall measurement show that these films are semiconductor. The obtained results imply that the growth of WC thin films is mainly from the atomic species(W and C) evaporated from the hot filament. The HW-CVD opens a novel route to synthesize wide band gap and conducting WC at a cost-efficient way for DSSCs and hydrogen evolution reaction (HER). (C) 2016 Elsevier B. V. All rights reserved.

Synthesis of gamma-WO3 thin films by hot wire-CVD and investigation of its humidity sensing properties - Jadkar, Vijaya; Pawbake, Amit; Waykar, Ravindra; Jadhavar, Ashok; Date, Abhijit; Late, Dattatray; Pathan, Habib; Gosavi, Suresh; Jadkar, Sandesh (Physica Status Solidi A-Applications and Materials Science, 2017)
In this study, monoclinic tungsten oxide (gamma-WO3) have been grown in a single step using HW-CVD method by resistively heating W filaments in a constant O-2 pressure. The formation of gamma-WO3 was confirmed using low angle-XRD and Raman spectroscopy analysis. Low angle-XRD analysis revealed that as-deposited WO3 film are highly crystalline and the crystallites have preferred orientation along the (002) direction. HRTEM analysis and SAED pattern also show the highly crystalline nature of WO3 with d spacing of similar to 0.38 nm, having an orientation along the (002) direction. Surface topography investigated by SEM analysis shows the formation of a uniform and homogeneous cauliflower like morphology throughout the substrate surface without flaws and cracks. A humidity sensing device incorporating WO3 is also fabricated, which shows a maximum humidity sensitivity factor of similar to 3954% along with a response time of similar to 14 s and a recovery time of similar to 25 s. The obtained results demonstrate that it is possible to synthesize WO3 in a single step by HW-CVD method and to fabricate a humidity sensor by using it. (C) 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim

Pressure-induced phase transitions in germanium telluride: raman signatures of anharmonicity and oxidation - Pawbake, Amit; Bellin, Christophe; Paulatto, Lorenzo; Beneut, Keevin; Biscaras, Johan; Narayana, Chandrabhas; Late, Dattatray J.; Shukla, Abhay (Physical Review Letters, 2019)
Pressure-induced phase transitions in GeTe, a prototype phase change material, have been studied to date with diffraction which is not sensitive to anharmonicity-induced dynamical effects. GeTe is also prone to surface oxidation which may compromise surface sensitive measurements. These factors could be responsible for the lack of clarity about the phases and transitions intervening in the phase diagram of GeTe. We have used high-pressure Raman scattering and ab initio pseudopotential density functional calculations to unambiguously establish the high-pressure phase diagram and identify three phases up to 57 GPa, a low-pressure rhombohedral phase, an intermediate pressure cubic phase, and a high-pressure orthorhombic phase. We detect substantial broadening and softening of Raman modes at low pressure and identify the transition regions and possible intermediate phases.